PENINGKATAN KOMPETENSI MENGIDENTIFIKASI ISI NOVEL REMAJA MELALUI MODEL MIINOLITRA THE DEVELOPMENT COMPETENCE TO IDENTITY THE CONTENT OF TEENAGER NOVEL THROUGH MIINOLITRA - Purwati, Panca Dewi (Balai Bahasa Jawa Tengah, 2017)
The three purposes that would be reached based on the problems in this research: 1) describing the characteristic of miinolitra studying model, 2) identifying the increasing of result studying, 3) describing the change of student?s behavior in class 8E SMP Negeri 33 Semarang. The approach used is class action research. This research was conducted in two ways. The result of this study is the class average 66.58 in pre-cycle step (done by 16 students), 76,56 in first step (done by 24 students). This thing shows that there is increasing of student?s goal 11.30. Wanted-to-know-everything behavior, cooperative, independent, and wishing of getting better score are also increasing. According to research result and journal analysis could be known that students behavior score in first step is, 4.25 (good category) and second step is 4,30 (good category). Key word: miinolitra model, identiftying novel, literature genre, JHS student.